ANALISIS FAKTOR KESEMBUHAN PASIEN KANKER DENGAN PENDEKATAN TERAPI DZIKIR DAN MURROTAL AL-QUR’AN: LITERATURE REVIEW - mustajab, abdullah azam; Fahrurozi, M; Marwiati, Marwiati (Jurnal Penelitian dan Pengabdian Kepada Masyarakat UNSIQ, 2025)
Introduction Cancer is the second leading cause of death in the world, causing 9.6 million deaths or 1 in 6 deaths. In Indonesia in 2020, according to Global Cancer Statistics (Globocan) data, there were 396,914 new cases of cancer with 234,511 deaths. The aim was to investigate the factors that influence the healing of cancer patients with spiritual therapy of dhikr and murrotal al-Qur'an. The method used in this study with a literature review on the Google Scholar database with a span of the last 10 years using several search keywords based on inclusion criteria including quantitative and qualitative research or mix-method, full-text and in Indonesian. While the exclusion criteria are not full-text and in languages ​​other than Indonesian. The results obtained factors that influence optimism for healing are social support and stress, factors that influence quality of life include dimensions of quality of life, physical dimensions, psychological dimensions, dimensions of social relationships and environmental dimensions. Cancer patients on average have high spirituality resulting in a higher religious well-being score than the existential well-being score. Meanwhile, the provision of spiritual therapy of dhikr and murrotal al-Qur'an on anxiety of cancer patients shows that there is a difference in anxiety scores before and after the intervention is given. Conclusion Spiritual therapy such as dhikr and murrotal al-Qur'an has an impact on increasing the psychological well-being of cancer patients, for example it can reduce pain, stress, depression and other psychological symptoms.